Visual culture - Boylan, Alexis L. (The MIT Press, 2020)
How to think about what it means to look and see: a guide for navigating the complexities of visual culture. The visual surrounds us, some of it invited, most of it not. In this visual environment, everything we see-color, the moon, a skyscraper, a stop sign, a political poster, rising sea levels, a photograph of Kim Kardashian West-somehow becomes legible, normalized, accessible. How does this happen? How do we live and move in our visual environments? This volume in the MIT Press Essential Knowledge series offers a guide for navigating the complexities of visual culture, outlining strategies for thinking about what it means to look and see-and what is at stake in doing so. Visual culture has always been inscribed by the dominant and by domination. This book suggests how we might weaponize the visual for positive, unifying change. Drawing on both historical and contemporary examples-from Judy Chicago's The Dinner Party and Beyoncé and Jay-Z at the Louvre to the first images of a black hole-Alexis Boylan considers how we engage with and are manipulated by what we see. She begins with what: what is visual culture, and what questions, ideas, and quandaries animate our approach to the visual? She continues with where: where are we allowed to see it, and where do we stand when we look? Then, who: whose bodies have been present or absent from visual culture, and who is allowed to see it? And, finally, when: is the visual detached from time? When do we see what we need to see?- Resumé vydavatel
Keywords: umění a společnost; vizuální kultura; art and society; visual culture; elektronické knihy; monografie; electronic books; monographs